Construction and optimization strategy of urban emergency logistics system - Jiang, Xiuhua; Hu, Die (International Journal of Global Economics and Management, 2024)
Emergency logistics has special logistics attributes, which will provide necessary emergency supplies for sudden public health events and natural disasters, reduce the degree of disaster losses, and pursue the maximization of time efficiency. Due to the characteristics of urban population distribution, the construction of efficient and orderly urban emergency logistics management mechanism is an important research field of emergency management system in the new era. Therefore, this paper first defines the concept and characteristics of emergency logistics, describes the constituent elements of emergency logistics, and deeply analyses the problems existing in the urban emergency logistics operation system, and finally conducts an in-depth exploration of the optimization strategy for the construction of urban emergency logistics system. It is hoped that it can provide certain reference for the relevant government departments, social enterprises and other parties involved in emergency logistics.